Visible light activated BINOL-derived chiroptical switches based on boron integrated hydrazone complexes. Issue 33 (10th August 2022) - van Vliet, Sven; Alachouzos, Georgios; de Vries, Folkert; Pfeifer, Lukas; Feringa, Ben L.
Abstract : Chiroptical switches, which use light to control chirality in a reversible manner, offer unique properties and fascinating prospects in the areas of molecular responsive systems, new photochromic materials and molecular data processing and storage. Abstract : Chiral optical switches, which use light to control chirality in a reversible manner, offer unique properties and fascinating prospects in the areas of molecular switching and responsive systems, new photochromic materials and molecular data processing and storage. Herein, we report visible light responsive chiroptical switches based on tetrahedral boron coordination towards an easily accessible hydrazone ligand and optically pure BINOL. Upon instalment of a non-planar dibenzo[ a, d ]-cycloheptene moiety in the hydrazone ligand's lower half, the enantiopure boron complex shows major chiroptical changes in the CD read-out after visible light irradiation. The thermal isomerization barrier in these chiroptical switching systems showed to be easily adjustable by the introduction of substituents onto the olefinic bond of the cycloheptene ring, giving profound control over their thermal stability. The control over their thermal stability in combination with excellent reversibility, photochemical properties and overall robustness of the complexes makes these BINOL-derived chiroptical switches attractive candidates for usage in advanced applications, e.g. photonic materials and nanotechnology.